Oceans Across the Solar System and the Search for Extraoceanic Life: Technologies for Remote Sensing and In Situ Exploration - Ved Chirayath; Elizabeth Bagshaw; Kate Craft; Heidi Heidi; Darlene Lim; Michael Malaska; Oscar Pizarro; Sam Purkis; Dustin Schroeder; Pablo Sobron; Sarah Waller; Dale Winebrenner (Oceanography, 2022)
Earth’s ocean comprises 99% of the habitable volume of our planet and contains the largest biomass and species diversity in the known universe. Perhaps unsurprisingly, recent advances in the search for life elsewhere in our solar system have increasingly pointed to potentially viable niches for life on other dynamic ocean worlds such as Titan, Europa, and Enceladus, among other moons of the outer gas giants. Indeed, the discovery of extraterrestrial life on these icy water bodies may motivate adopting an altogether new terminology and further non-anthropic perspective on the cosmos for what may well prove to be an abundant and diverse extraoceanic life, to coin a term. Exploration of such ocean worlds across the solar system will undoubtedly be enabled by technological developments in a range of sensing methodologies primarily developed for oceanography on Earth. As we have learned studying our home ocean, where less than 10% of the benthic surface has been optically imaged, the challenge is daunting, yet recent advances give hope. Here, we review some of the state-of-the-art techniques from oceanography and planetary science that may inform sensing of the biological and geophysical properties of ocean worlds, ranging from large-scale synoptic views afforded by active and passive remote sensing to in situ autonomous sampling and methods for detecting biosignatures.

Temporal expression of sex-specific genes in the mantle of the common mussel (Mytilus edulis) - Wael F. Sedik; Kate E. Dempsey; Xiang Meng; John A. Craft (Marine Biology, 2010)